Training Programs for Reducing Body Circumference of Patients with Obesity (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
Obesity is a disease with a significant increasing prevalence that affects body circumference and becomes an indicator of health measurement. Exercise programs need to be given to determine the effectiveness of the program on the changes in body circumference of patients with obesity status, such as PIR Fit Journey which applies High Intensity Interval Training exercise with 2-month duration. The research method used quantitative approach with pre-experimental one group pre-test post-test design. Subjects were employees of Pertamina International Refinery with adiposity. The total samples were 11 samples taken from 63 population. The main characteristics included body weight exceeding 70kg for men and women. The subjects were selected using purposive sampling technique. The data obtained included age, gender, upper arm, waist, and thigh circumference measured using a body meter. The data analysis test used in the study was a non-parametric test because the subject n= 30. The appropriate non-parametric test is the Wilcoxon paired test because the pre-test and post-test data were from the same subject. The results showed the effectiveness of the exercise program with significant changes. The upper arm circumference was 39.27 ± 10.77 for pre-test data and 32.64 ± 2.96 Δ -6.64 ρ .05 for post-test data. The waist circumference was 106.44 ± 11.39 for pre-test data and 96.36 ± 9.10 Δ -10.08 ρ .05 for post test data. However, the data were not significant in thigh circumference. The pre-test result was 52.63 ± 13.72 and the post-test result was 56.60 ± 7.46 Δ +3.98 ρ .05. It concludes that PIR Fit Journey program was effective in reducing upper arm and waist circumference, but there was no significant change in thigh circumference of the subjects.